Conservation of Imprinting and Methylation of MKRN3, MAGEL2 and NDN Genes in Cattle - Li, Junliang (Animals (Basel), 2021)
SIMPLE SUMMARY: In mammals, imprinted genes play key roles in embryonic growth and postnatal behavior and their misregulation has been associated with several developmental syndrome and cancers. At present, more than 150 imprinted genes have been identified in humans and mice. Cattle is an economically important farm animal, but compared to humans and mice, few genes have been reported as imprinted in this species. MKRN3, MAGEL2 and NDN are three maternally imprinted genes in the human Prader-Willi and Angelman syndromes imprinted locus at 15q11-q13. In this study, we determined that the bovine MKRN3, MAGEL2 and NDN genes are three paternally expressed gene, and their expression is regulated by the DNA methylation. This work could advance the genomic imprinting by increasing the knowledge of imprinted genes in bovine and also facilitate future studies to detect the physiological roles of MKRN3, MAGEL2 and NDN genes. ABSTRACT: Genomic imprinting is the epigenetic mechanism of transcriptional regulation that involves differential DNA methylation modification. Comparative analysis of imprinted genes between species can help us to investigate the biological significance and regulatory mechanisms of genomic imprinting. MKRN3, MAGEL2 and NDN are three maternally imprinted genes identified in the human PWS/AS imprinted locus. This study aimed to assess the allelic expression of MKRN3, MAGEL2 and NDN and to examine the differentially methylated regions (DMRs) of bovine PWS/AS imprinted domains. An expressed single-nucleotide polymorphism (SNP)-based approach was used to investigate the allelic expression of MKRN3, MAGEL2 and NDN genes in bovine adult tissues and placenta. Consistent with the expression in humans and mice, we found that the MKRN3, MAGEL2 and NDN genes exhibit monoallelic expression in bovine somatic tissues and the paternal allele expressed in the bovine placenta. Three DMRs, PWS-IC, MKRN3 and NDN DMR, were identified in the bovine PWS/AS imprinted region by analysis of the DNA methylation status in bovine tissues using the bisulfite sequencing method and were located in the promoter and exon 1 of the SNRPN gene, NDN promoter and 5’ untranslated region (5’UTR) of MKRN3 gene, respectively. The PWS-IC DMR is a primary DMR inherited from the male or female gamete, but NDN and MKRN3 DMR are secondary DMRs that occurred after fertilization by examining the methylation status in gametes.